Analysis of Exponentially Increasing Dependent Wave Amplitude of Peristaltic Pumping of Casson Fluid through Channels - Singh, Amirlal; Tiwari, Shailendra Kumar (Discontinuity, Nonlinearity, and Complexity, 2026)
This investigation is made to study the effect of exponentially increasing wave amplitude on swallowing of such food stuffs which behave as Casson fluid. Highly concentrated fluids such as tomato puree, jelly, soup, honey etc has been considered. The dependence of pressure on space and time has been investigated for time averaged flow rate. The magnitude of the pressure along the length of oesophagus increases with the larger wave amplitude amplifying parameter at all temporal values. It is also observed that the difference between the maximum and the minimum pressures at the distal end becomes greater when amplitude increases exponentially.